The relationship between maternal uterine artery doppler ultrasound during the second and third trimesters and infant cognitive development at one year of age: Findings from a South African prospective cohort study - Sydni A. Weissgold; Noha Ibrahim; Lucy Brink; Amy J. Elliott; Eva Loth; Vaheshta Sethna; Hein Odendaal (PLoS ONE, 2025)
Introduction Increased resistance to uterine artery blood flow is an index for poor pregnancy outcomes. This study aimed to examine the association between maternal uterine artery pulsatility index and cognitive development in infants aged one year, and whether placental dysfunction moderates this relationship. Methods This was a prospective cohort study in an economically deprived community in South Africa. 1297 pregnant women with singleton gestations and their term infants were assessed. uterine artery pulsatility index, assessed by Doppler ultrasound in the second and third trimesters of pregnancy were examined. Placental dysfunction is indicated by maternal vascular malperfusion and accelerated villous maturation of the placenta. The primary outcome was infant cognitive development, assessed by the composite score of the Mullen Scales of Early Learning, at one year of age. Results Higher uterine artery pulsatility index was associated with lower cognitive scores, when adjusting for alcohol consumption and antenatal depression in the second trimester (β = −0.086, p = 0.007), explaining 5% of the variance in the model. There was no evidence of moderation by maternal vascular malperfusion or accelerated villous maturation of the placenta. Conclusions Abnormal uterine artery pulsatility indices during the second trimester is associated with cognitive development in infants.